Implementasi Pendidikan Inklusif Berbasis Ukhuwah di TMI Al-Amien Prenduan dalam Menguatkan Toleransi dan Nasionalisme sebagai Fondasi Peradaban Multikultur - Hufron, A; Warits, Abd; Halim, Abd.; Harmonika, Sri; Yahya, Fizian; Aziz, Abdul (At-Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
Inclusive education is a strategic approach to fostering a harmonious society amidst Indonesia’s diverse cultures and religions. This research analyzes the implementation of inclusive education at Tarbiyatul Mu’allimin Al-Islamiyyah (TMI) Al-Amien Prenduan. The study’s goal is to understand how the school internalizes Islamic values, nationalism, and tolerance. We used a qualitative, case study design, gathering data through in-depth interviews with school leaders, teachers, and students, along with participant observation and document analysis. Thematic analysis and source triangulation ensured data validity. Findings reveal that TMI Al-Amien successfully implements inclusive education by integrating the principles of ukhuwah islamiyyah (Islamic brotherhood) and ukhuwah wathaniyyah (national brotherhood) throughout its educational aspects. The curriculum accommodates diverse student backgrounds while maintaining Islamic identity. A holistic evaluation system assesses academics, personality, and social skills, indicating success. Challenges like student heterogeneity, potential group exclusivity, and limited media literacy were overcome by strengthening core values, developing educator competencies, and encouraging multicultural interaction. We conclude that TMI Al-Amien’s inclusive education model effectively strengthens student tolerance and nationalism, serving as a valuable reference for multicultural education development in other pesantren